KEJADIAN STUNTING DENGAN PERKEMBANGAN ANAK USIA 2-3 TAHUN DI KOTA TERNATE - Sari Prihatin; Eni Sulastri (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2022)
Abstract Stunting is a primary health problem in Indonesia. The percentage of nutritional status according to the data taken from the Basic Health Research in Indonesia, 2018, for severely stunted and stunted under-two-year-old children was 29.9% and the proportion in North Maluku province was more than >25%. The percentage of stunting in Ternate reached 24.4% in 2017. This number is still considered high compared to the prevalence standard of stunted under-five children according to WHO. This study aimed to analyze the relationship between stunting prevalence and two or three-year-old children’s growth in Ternate. This was an analytical and observational study with a cross-sectional approach. The population in this study was children aged 2-3 years old who suffered from stunting in Ternate. The sampling technique was census (non-probability sampling) and the data collection was done using questionnaires. The data were analyzed using both univariate and bivariate analyses known as the Coefficient Contingency test. The result based on the result of the Coefficient Contingency test showed that the stunting prevalence against the growth of children aged 2 or 3 years old was 0.247 with a p-value of 0.364. Conclusion: there is a relationship between stunting and a child’s growth in Ternate. Keywords: Stunting, Child’s Growth Abstrak Stunting merupakan masalah kesehatan masyarakat utama di Indonesia. Presentasi status gizi meurut Data Riskesdas Tahun 2018 di Indonesia proporsi status gizi sangat pendek dan pendek pada Baduta yaitu 29,9 % dan di Provinsi Maluku Utara >25 % . Stunting di Kota Ternate mencapai 24,4 % pada tahun 2017 , angka ini masih tinggi jika dibandingkan dengan standar prevalensi balita pendek menurut WHO. Tujuan penelitian ini adalah menganalisis hubungan kejadian stunting dengan perkembangan anak usia 2-3 tahun di Kota Ternate. Penelitian ini merupakan penelitian analitik observasional dengan pendekatan cross sectional study. Populasi dalam penelitian ini adalah anak usia 2-3 tahun yang mengalami stunting di Kota Ternate. Teknik pengambilan sampel adalah menggunakan sensus (non probability sampling) dan Teknik pengumpulan menggunakan kuesioner. Analisis data yaitu univariate dan bivariate yaitu uji Coefficient Contingency. Hasil penelitian menunjukkan bahwa hasil analisis Coefficient Contingency antara kejadian stunting dengan perkembangan pada anak usia 2-3 tahun adalah 0,247 dengan p value 0,364. Kesimpulan : ada hubungan antara Stunting dengan perkembangan anak di Kota Ternate. Kata Kunci : stunting, perkembangan anak